2012
DOI: 10.1097/sap.0b013e31826239f0
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Application of Human Adipose Tissue–Derived Mesenchymal Stem Cells in Progressive Hemifacial Atrophy (Parry-Romberg Disease) With Microfat Grafting Techniques Using 3-Dimensional Computed Tomography and 3-Dimensional Camera

Abstract: Adipose-derived stem cells enhance the survival of fat grafted into the face. A microfat graft with simultaneous ASC injection may be used to treat Parry-Romberg disease without the need for microvascular free flap transfer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
87
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(93 citation statements)
references
References 17 publications
0
87
0
6
Order By: Relevance
“…En segundo lugar citamos otro ensayo clínico aleatorizado publicado por Kyung Suk Koh (14) en Corea del Sur. Este autor toma 10 pacientes con diagnóstico de enfermedad de Parry-Romberg y los asigna de manera aleatorio a 2 grupos, cada uno con 5 pacientes.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…En segundo lugar citamos otro ensayo clínico aleatorizado publicado por Kyung Suk Koh (14) en Corea del Sur. Este autor toma 10 pacientes con diagnóstico de enfermedad de Parry-Romberg y los asigna de manera aleatorio a 2 grupos, cada uno con 5 pacientes.…”
Section: Resultsunclassified
“…Finalmente, el recientemente publicado ensayo aleatorizado de Kyung Suk Koh (14), con nivel de evidencia 2B, incluye 10 pacientes a los que distribuye en 2 grupos, cada uno de 5 pacientes, para recibir lipoinjerto enriquecido o convencional y sigue durante 18 meses. Introduce además de las variables subjetivas de satisfacción del paciente tenidas en cuenta por Sterodimas, mediciones objetivas del comportamiento del lipoinjerto en el tiempo con respecto al porcentaje de reabsorción evaluado mediante TAC tridimensional y cámara fotográfica que realiza también reconstrucción tridimensional.…”
Section: Discussionunclassified
“…Through non-clinical and clinical studies on Buerger's disease, Perry-Romberg disease [1], and critical limb ischemia [2], the authors have already confirmed the revascularization of adipose stem cells and the possibility of treatment via anti-inflammatory reactions. We have also presented clinical results for degenerative arthritis [3].…”
Section: Introductionmentioning
confidence: 97%
“…In particular, it has to be considered seriously that concerns about the possibility of cancer development derived from cultured autologous adipose stem cells. The reasons for concerns about the possibility of cancer promotion by the administration of cultured adipose stem cells [8,9] are as follows: (1) genetic mutations may occur during the culturing process and (2) the growth factors secreted by stem cells may promote the growth of cancer cells and create a favorable environment for them. However, several reports have presented that stem cells inhibit cancer development [10][11][12], which suggests the importance of discerning the characteristics of cultured stem cells.…”
Section: Introductionmentioning
confidence: 99%
“…It characteristically involves the skin and subcutaneous connective tissues and may later progress to affect the underlying musculature, cartilage, and osseous structures with or without development of neurologic symptoms. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]23,26 PRS typically presents initially in children and young adults and slowly progresses over a highly variable course ranging from 2 to 20 years, eventually reaching a "burned-out phase" and stabilizing for no apparent reason. [2][3][4][5][6][8][9][10][14][15][16][17] This peculiar disease course, along with highly variable signs and symptoms, impedes consistent understanding of the underlying pathophysiology of PRS.…”
mentioning
confidence: 99%